Happier during lockdown: A descriptive analysis of self-reported wellbeing in 17,000 UK school students during Covid-19 lockdown - Soneson, E; Puntis, S; Chapman, N; Mansfield, K; Jones, PB; Fazel, M (Springer, 2022)
Relatively little research has focused on children and young people (CYP) whose mental health and wellbeing improved during Covid-19 lockdown measures. We aimed to (1) determine the proportion of CYP who self-reported improvement in their mental wellbeing during the first Covid-19 lockdown and (2) describe the characteristics of this group in relation to their peers. We conducted a descriptive analysis of data from the 2020 OxWell Student Survey, a self-report, cross-sectional survey of English CYP. A total of 16,940 CYP primarily aged 8–18 years reported on change in mental wellbeing during lockdown. We characterised these CYP in terms of school, home, relational, and lifestyle factors as well as feelings about returning to school. One-third (33%) of CYP reported improved mental wellbeing during the first UK national lockdown. Compared with peers who reported no change or deterioration, a higher proportion of CYP with improved mental wellbeing reported improved relationships with friends and family, less loneliness and exclusion, reduced bullying, better management of school tasks, and more sleep and exercise during lockdown. In conclusion, a sizeable minority of CYP reported improved mental wellbeing during lockdown. Determining the reasons why these CYP felt they fared better during lockdown and considering how these beneficial experiences can be maintained beyond the pandemic might provide insights into how to promote the future mental health and wellbeing of school-aged CYP. All those working with CYP now have an opportunity to consider whether a systemic shift is needed in order to understand and realise any learnings from experiences during the pandemic.